Designing a Clinical Study With Dietary Supplements: It's All in the Details - Floyd, Z. Elizabeth; Ribnicky, David M.; Raskin, Ilya; Hsia, Daniel S.; Rood, Jennifer C.; Gurley, Bill J. (Frontiers in Nutrition, 2022)
A successful randomized clinical trial of the effect of dietary supplements on a chosen endpoint begins with developing supporting data in preclinical studies while paying attention to seemingly insignificant details when planning the related clinical trial. In this perspective, we draw on our experience studying the effect of an ethanolic extract from Artemisia dracunculus L. (termed PMI-5011) on glucose homeostasis as a potential therapeutic option in providing resilience to obesity-related Metabolic Syndrome. Decisions on experimental design related to issues ranging from choice of mouse model to dosing levels and route of administration in the preclinical studies will be discussed in terms of translation to the eventual human studies. The more complex considerations in planning the clinical studies present different challenges as these studies progress from testing the safety of the dietary supplement to assessing the effect of the dietary supplement on a predetermined clinical outcome. From the vantage point of hindsight, we will outline potential pitfalls when translating preclinical studies to clinical studies and point out details to address when designing clinical studies of dietary supplements.